Orders and Sequences in the Acquisition of L2 Morphosyntax, 40 Years On: An Introduction to the Special Issue - Hulstijn, J.; Ellis, Rod; Eskildsen, S. (2015)
This Special Issue of Language Learning provides a state-of-the-art overview of current perspectives on acquisition orders and sequences in second language acquisition. It contains examples of empirical studies, theoretical reflections of, and a dialogue between proponents of Dynamic Systems Theory, Learner Varieties, Processibility Theory, Processing Determinism, Sociocultural Theory, and Usage-Based Linguistics. This introduction presents the context and rationale for the collection of contributions.